Immersive virtual reality for language education : examining teacher perspectives and implementation ideas for university foreign language learning environments - De Sanctis, Francesca (2024)
Virtual reality (VR) has shown potential as a tool for improving the quality of language education (LE). High-immersion VR (iVR) in particular has emerged as promising for its affordance of authentically recreating real-life scenarios and inducing a higher sense of physical presence in the immersive virtual environment (iVE). Acknowledging the role of teachers as crucial actors in the process of implementing a new technology in a pedagogically-relevant way, this study focused on understanding how foreign language (FL) teachers perceive iVR and four tested iVR apps. A workshop on iVR for LE was used as a first step in a design-based research (DBR) approach to investigate 8 university FL teachers’ perspectives before and during the workshop. Insights were gathered on perceived affordances and limitations of tested iVEs, together with implementation-related aspects. Main identified assets of tested iVEs were that they allow to practise the language without the drawbacks of real life situations, can provide multimodal and gamified experiences, help develop interaction and presentation skills, and support vocabulary acquisition. Among identified challenges to iVR implementation were a lack of familiarity with the technology, technical issues and a lack of resources. Participants thought iVEs might help with current perceived challenges in the classroom, for example by providing opportunities to interactively practise the language, reducing foreign language anxiety and promoting authentic communication in online meetings. Finally, identified types of support teachers would need to implement iVR in their own teaching belonged to the categories of external and internal resources. These results will provide suggestions for future steps in critical evaluation and implementation of iVR solutions for LE.